Development of Task Implementation Evaluation System Online Classroom Guardians with Extreme Programming Methods at The Noble Foundation Consortium - Wahid, Abdul; Mulyanto, Agus (IJID (International Journal on Informatics for Development), 2017)
Evaluating the performance of employees in an organization is a necessity if the organization seeks improvement of their service quality. Konsorsium Yayasan Mulia working in the field of education is very concerned with evaluating their employee performance. One of the evaluations which have been routinely carried out is evaluation of homeroom teacher performance. This evaluation is done as a form of Konsorsium Yayasan Mulia attention on the student character building. The evaluation has been made manually spend a lot of time and effort, it is necessary for a system that can be the solution of the problem. The system will be built is the first system, that means it requires development method that flexible to changes.System development method used in this research is eXtreme Programming. This method is part of Agile Programming that emphasizes intense communication with customers to determine their needs. The steps of this method are planning, design, coding and testing.The homeroom task evaluation system is a bridge between the homeroom teacher, the principal and Konsorsium Yayasan Mulia. General overview of the system, the system has three user level, admin, principal and homeroom teacher. Admin can post an evaluation sheet and manage principal. Principal can manage homeroom teacher and homeroom theacher can report their task performance.The result of this research is a system that provides convenience to Konsorsium Yayasan Mulia to evaluate the task performance of homeroom teacher.